Beyond pathogenicity: applications of the type III secretion system (T3SS) of Pseudomonas aeruginosa - Su, Tianqi; Zhang, Lin; Shen, Jie; Qian, Danyu; Guo, Yulei; Li, Zhenpeng (Frontiers in Microbiology, 2025)
The Gram-negative opportunistic pathogen Pseudomonas aeruginosa employs its type III secretion system (T3SS) as a pivotal factor in facilitating the injection of effector proteins into host cells. This process disrupts cellular machinery and immune responses, thereby increasing the pathogen’s survival rates. Recent advancements across multiple disciplines have broadened the scope of T3SS research, extending beyond mechanistic investigations to encompass diverse applications in anti-infective therapies, vaccine development, and protein delivery systems. This comprehensive review analyzes the molecular structure and regulatory mechanisms of T3SS, while also exploring its emerging biomedical applications, which include: (1) the development of antimicrobial agents that target T3SS; (2) T3SS-based vaccines; and (3) T3SS-mediated delivery systems. Furthermore, the review discusses current challenges, particularly focusing on the translational hurdles that hinder clinical application.